Diversity, phylogeny and biogeography of Systomus (Teleostei, Cyprinidae) in Sri Lanka - Hiranya Sudasinghe; Rohan Pethiyagoda; Rajeev Raghavan; Neelesh Dahanukar; Lukas Rüber; Madhava Meegaskumbura (Zoologica Scripta, 2020)
The South and South‐East Asian freshwater fish genus Systomus (Cyprinidae) comprises 17 valid species. Six nominal species, including three endemics, have been reported from Sri Lanka, a continental island separated from India by a shallow‐shelf sea. The species diversity of Systomus on the island has until now not been assessed; neither has an evaluation been made of their phylogenetic history. Here, based on an analysis of the nuclear recombination activating protein 1 ( rag1 ), and mitochondrial cytochrome c oxidase subunit 1 ( cox1 ) and cytochrome b ( cytb ) gene markers, and a morphological examination of 143 specimens from 49 locations in Sri Lanka, we reassess the diversity of Systomus on the island and analyse patterns of their evolution and biogeography. Divergence‐time estimates, based on a substitution rate calibration, date the basal split between Systomus and its sister group, the Afrotropical small barbs, to 30.0 Ma (95% highest posterior density: 25.4–35.2 Ma). The species of Systomus belong to two distinct clades. The first includes the Sri Lankan endemics S. asoka, S. martenstyni and S. pleurotaenia , which comprise an insular diversification following the immigration of a common ancestor during the Oligocene. The second, which includes the remaining species of Indian, Sri Lankan and South‐East Asian Systomus , has a crown age dating to the Late Miocene. Morphological and molecular species delimitation analyses failed to validate the two nominal species, S. spilurus and S. timbiri , previously reported from Sri Lanka: both are considered synonyms of S. sarana , as are the nomina S. chryseus, S. chrysopoma, S. laticeps, S. rufus, S. pinnauratus and S. subnasutus . Four genetically and geographically discrete lineages of S. sarana occur in the island, and three in India. Molecular species delimitation analysis suggests these all belong to a single species, S. sarana . The genetically distinct Sri Lankan populations of S. sarana result from Plio‐Pleistocene dispersal or vicariance events between India and Sri Lanka—as a result of emergence and inundation of the now submerged isthmus connecting the two landmasses—as well as autochthonous insular diversification.